Effects of sleep deprivation on component processes of working memory in younger and older adults. Issue 3 (18th January 2018) - Pasula, Elissa Y; Brown, Gregory G; McKenna, Benjamin S; Mellor, Alix; Turner, Travis; Anderson, Clare; Drummond, Sean P A
Abstract: Study Objectives: Working memory (WM) has been described as a multicomponent process, comprised of the following: attention-driven encoding, maintenance and rehearsal of information, and encoding to and retrieval from episodic memory. Impairments can affect higher-order cognitive processes and many everyday functions. The impact of sleep changes on these cognitive processes across the life span needs to be investigated. The aim of the current study is to examine the effects of sleep deprivation on component processes of WM, comparing younger and older adults across verbal and visuospatial modalities. Methods: Thirty-one younger adults (19–38 years) and 33 older adults (59–82 years) attended two counterbalanced sleep protocols: a regular night of sleep followed by testing the next day (normally rested condition), and 36 hr of total sleep deprivation (TSD), followed by testing (TSD condition). Participants completed matched versions of verbal and visuospatial WM tasks across conditions. Results: Younger adults significantly outperformed older adults on encoding and displacement component processes, for both verbal and visuospatial WM. Following TSD, younger adults showed a significantly larger drop compared with older adults in verbal encoding and in visuospatial displacement. A main effect of condition was observed for verbal displacement. Conclusions: Differences were observed in the performance of younger and older adults on component processes of WM following TSD. This suggests that TSD can have differential effects on each component process when younger and older adults are compared, in both verbal and visuospatial tasks. Understanding this profile of changes is important for the development of possible compensatory strategies or interventions and the differentiation of clinical and healthy populations.